Motion iconicity in prosody - Ekström, Axel G.; Nirme, Jens; Gärdenfors, Peter (Frontiers in Communication, 2022)
Recent evidence suggests that human nonverbal speech may be rich in iconicity. Here, we report results from two experiments aimed at testing whether the perception of increasing and declining f0 can be iconically mapped onto motion events. We presented a sample of mixed-nationality participants (N=118) with sets of two videos, where one pictured ascending movement and the other descending movement. A disyllabic nonsense word prosodically resynthesized as increasing or declining in f0 was presented simultaneously with each video in a pair, and participants were tasked with guessing which of the two videos the word described. Results indicate that prosody is iconically associated with motion, such that motion-prosody congruent pairings were more readily selected than incongruent pairings (p<.033). However, the effect observed in our sample was primarily driven by the selections of words with declining f0. A follow-up experiment with native Turkish speaking participants (N=92) tested for the effect of language-specific metaphor for auditory pitch. The results of the follow-up experiment showed no significant association between prosody and motion. Some implications for the motor theory of speech perception, and “gestural origins” theories of the evolution of human language, as well as limitations of the present paradigm, are discussed.